A influência cultural portuguesa na reorganização do espaço da microrregião geográfica de Cruz Alta/RS - Caetano, Jessica Nene (2012)
This research focuses on analyzing the contribution of Portuguese culture and its influence on the organization of space at the Geographic Microregion of Cruz Alta-RS, investigating the social development in the course of its evolutionary process linked to the spatio-temporal dynamics by cultural bias. As hasintrinsic goals of this research are: (a) analyze the process of settlement at the Geographic Microregion of Cruz Alta by Portuguese culture, identifying key milestones that resulted in the temporal and spatial reorganization in cultural transformations and (b) identify the major cultural codes Portuguese on the landscape expressed in the analyses of the Microregion which are responsible for the identification process of this social group. To achieve the proposed objectives were used bibliographies relating to the subject in question, data from secondary sources and field work. Later, it was the data analysis and final draft of the dissertation. As a result, this research found that the inclusion of material and immaterial codes of Portuguese ethnicity has not been effected only with the arrival of immigrants from Portugal, but by the Luso-Brazilian settlement and Azorean colonization in the Geographic Micoregion of Cruz Alta, if consolidated as a Lusitanian cultural matrix. It should be noted, also, that this study allowed to state that its culture, regard to the manifestation of its material and immaterial culture presents itself today as absent in the landscape of MRG 011, with the exception of Cruz Alta, which still manifests the peculiarities of this ethnic group. It is evident that this research is part of the concerns relating to Cultural Geography, seeking to relate culture and space in an interdisciplinary way.